DAMPAK PENGELUARAN WISATAWAN DOMESTIK TERHADAP PEREKONOMIAN JAWA BARAT - Harahap, Agustin; Andjanie, Isabella Fitria; Fatmasari, Baiq Rizky; Pratiwi, Wiwik Dwi (Jurnal Master Pariwisata (JUMPA); Volume 10, Nomor 01, Juli 2023, 2023)
Tourism is a sector that is not defined as a distinct sector in the economic statistics of West Java Province, which results in the contribution of tourism not being clearly visible. As a result, the tourism sector is severely disadvantaged by the lack of data showing its full economic impact. Therefore, this study tries to see the impact of tourism on the West Java economy based on domestic tourist expenditure in 2021. Quantitative approach and input output model analysis are used to see the economic impact of tourism by estimating the multiplier effect of domestic tourist spending on output, income, gross value added, and employment. The results of this study indicate that tourism has had a major impact and is one of the important industries in the West Java economy, which contributed 9.28% to GRDP and 12.39% of the total working population in West Java in 2021. Keywords: nput-Output model; economy impact; tourism industry; multiplier; domestic tourist expenditure.